After 20 years of low fertility, where are the obstetrician-gynecologists? - Se Jin Lee; Lan Li; Jong Yun Hwang (Korean Society of Obstetrics and Gynecology, 2021)
Korea has entered a stage of low fertility, with a total fertility rate of 1.178 in 2002 and 0.92 in 2019. The low birth rate has led to the closure of obstetric hospitals and clinics from 1,371 maternity health facilities in 2003 to 541 in 2019, which is 39.5% compared to 2003. Since 2011, the Ministry of Health and Welfare has been operating an "Obstetrically Underserved Areas Support Project," however, a shortage of obstetrician-gynecologists (OB/GYNs) who can participate in labor and delivery is a major problem. In 2019, there were 5,800 OB/GYNs practicing. Of these, 4,225 (72.8%) were working in obstetrics-gynecology hospitals, each responsible for 2,855 fertile women. Their average age was 51.8 years. A total of 2,659 (45.9%) worked in clinics and 3,110 (73.6%) were working in metropolitan districts. Only 124 OB/GYNs (2.9%) worked in vulnerable rural areas. OB/GYNs working in obstetric hospitals were responsible for 113.8 newborns in 2019. Their average age was 50.1 years. Of them, 67.4% were working in hospitals, 74.1% in urban areas, and only 60 specialists (2.3%) were working in rural areas. To establish a safe childbirth environment during an era of low fertility, it is important to have obstetricians in charge of childbirth. The government should establish a comprehensive long-term plan to resolve the shortage of OB/GYNs.